The Implementation and Lasting Effects of the Multilateral Instrument. - Kofler, Georg (European and international tax law and policy series, 2021)
Action 15 of the BEPS Project "The Multilateral Convention to Implement Tax Treaty Related Measures to Prevent Base Erosion and Profit Shifting? - the Multilateral InstruƯment (MLI)" is a multilateral convention that swiftly modifies the application of existing bilateral tax treaties without the need to renegotiate each treaty individually. It does not replace the existing tax treaties but rather modifies their application with the aim to reduce the opportunities for tax avoidance by multinational enterprises, counter treaty abuse and improve the dispute resolution mechanism, providing flexibility according to the different treaty policies and positions chosen by countries. The MLI was finalized in November 2016, and a first signing ceremony was held in Paris on 6 June 2017. A total of 76 jurisdictions signed it at this first ceremony. In the meantime, it has grown to cover almost 100 jurisdictions. The aim of this book is to provide tax authorities, policymakers, courts and practitioners with an overview of the countries' positions and experiences regarding the impact of the MLI on their tax treaty network, as well as other issues on the implementation of the convention with respect to policy options, reservations, and legal and constitutional concerns. The book comprises 34 national reports from countries across the globe and is the outcome of an alternative non-physical interaction between national reporters and authors. This was due to the special COVID-19 situation lived during 2020, serving as a substitute for the prepared conference on the MLI that should have taken place from 2 to 4 July 2020 in Rust, Burgenland, Austria. A general report highlights the most important findings.